1999
DOI: 10.1074/jbc.274.44.31456
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Interaction Between Murine IgA and Murine Secretory Component Carrying Epitope Substitutions Reveals a Role of Domains II and III in Covalent Binding to IgA

Abstract: We have identified sites for epitope insertion in the murine secretory component (SC) by replacing individual surface-exposed loops in domains I, II, and III with the FLAG sequence (Crottet, P., Peitsch, M. C., Servis, C., and Corthé sy, B. (1999) All three loops, referred to as B-C, D-E, and F-G in domain I are particularly implicated in binding to IgA (4, 5); in addition, some residues of loop E-F in the opposite face appear to be important for IgA binding. In contrast, deletion of domains II and III or ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…8C). Thus the SIgA2 structure is consistent with the proposal for SIgA1 in which a "zipper effect" association of the unbound J-shaped SC domain structure occurs along the edge of the Fc regions (20,46). The lack of the extended hinge in SIgA2 does, of course, mean that SIgA2 cannot perform the functions mediated by the O-linked sugars of the IgA1 hinge that serve as ligands for cellular receptors and bind pathogens such as S-fimbriated Escherichia coli (47,48).…”
Section: Discussionsupporting
confidence: 65%
“…8C). Thus the SIgA2 structure is consistent with the proposal for SIgA1 in which a "zipper effect" association of the unbound J-shaped SC domain structure occurs along the edge of the Fc regions (20,46). The lack of the extended hinge in SIgA2 does, of course, mean that SIgA2 cannot perform the functions mediated by the O-linked sugars of the IgA1 hinge that serve as ligands for cellular receptors and bind pathogens such as S-fimbriated Escherichia coli (47,48).…”
Section: Discussionsupporting
confidence: 65%
“…Because EPEC adhesion molecule intimin possesses Ig-like domains and a terminal C-type lectin-like domain (29, 30), we postulated that (i) such domains might associate with similar domains (31)(32)(33) and/or glycans displayed by hSC and (ii) such an interaction would alter the intimin-dependent EPEC adhesion as reflected by the formation of A/E lesions (34). In preliminary in vitro binding experiments, we observed that in the presence of hSCrec, the adhesion of wild type EPEC to target HEp-2 cells was reduced to levels comparable with those found with the int Ϫ EPEC mutant (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The "docking site" on IgA for Fc␣RI has been mapped to the boundary of CH2 and CH3 (38,39), a location occupied by SC (40). To evaluate the effect of SC on IgA-Fc␣RI binding, we fractionated IgA1 isolated from supernatants of IgA1-J-SC and that of IgA2-J-transfected BHK cells.…”
Section: Discussionmentioning
confidence: 99%